Current therapy option for necrotizing enterocolitis: Practicalities and challenge - Wu, Huihuan; Guo, Kehang; Zhuo, Zewei; Zeng, Ruijie; Luo, Yujun; Yang, Qi; Li, Jingwei; Jiang, Rui; Huang, Zena; Sha, Weihong; Chen, Hao (Frontiers in Pediatrics, 2022)
Necrotizing enterocolitis (NEC) is one of the most prevalent neonatal gastrointestinal disorders. Despite ongoing breakthroughs in its treatment and prevention, the incidence and mortality associated with NEC remain high. New therapeutic approaches, such as breast milk composition administration, stem cell therapy, immunotherapy, and fecal microbiota transplantation (FMT) have recently evolved the prevention and the treatment of NEC. This study investigated the most recent advances in NEC therapeutic approaches and discussed their applicability to bring new insight to NEC treatment.